2021
DOI: 10.3390/nu13082501
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Hypocholesterolemic Actions of Protamine-Derived Peptide RPR (Arg-Pro-Arg) and Protamine in High-Fat Diet-Induced C57BL/6J Mice

Abstract: Dietary protamine can ameliorate hyperlipidemia; however, the protamine-derived active peptide and its hypolipidemic mechanism of action are unclear. Here, we report the discovery of a novel anti-obesity and hypocholesterolemic peptide, RPR (Arg-Pro-Arg), derived from protamine in mice fed a high-fat diet for 50 days. Serum cholesterol levels were significantly lower in the protamine and RPR groups than in the control group. White adipose tissue weight was significantly decreased in the protamine and RPR group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The blood samples for analyses of TC, HDL-cholesterol and LDL-cholesterol were collected at the time of euthanasia for all articles except one, where blood samples were collected 1 week prior to euthanasia (35) . Blood was sampled from fasting rats in the majority of the articles (31,32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) , while twelve articles declared that animals were not fasted (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) . Two articles presented results where half of the rats in each of the experimental groups were non-fasting while the rest of the animals were in a fasting state (66,67) , and four articles did not include information about the prandial state of the animals (35,(68)(69)(70) .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood samples for analyses of TC, HDL-cholesterol and LDL-cholesterol were collected at the time of euthanasia for all articles except one, where blood samples were collected 1 week prior to euthanasia (35) . Blood was sampled from fasting rats in the majority of the articles (31,32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) , while twelve articles declared that animals were not fasted (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) . Two articles presented results where half of the rats in each of the experimental groups were non-fasting while the rest of the animals were in a fasting state (66,67) , and four articles did not include information about the prandial state of the animals (35,(68)(69)(70) .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Most of the included studies were designed with ad libitum access to feed (31,32,34,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)48,50,53,54,56,59,62,63,65,66,68) . The remaining studies were designed with pair feeding (49,64) , slightly restricted access to feed (67) or gave no information on whether feed was freely available or controlled (35,47,51,52,57,58,60,61,69,70) .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to determine whether the LPH was able to restore the altered lipid profile by the WD; for this motif, the SD group was necessary only to confirm that the WD ingestion induces an alteration of this profile, according to other study designs. 25,[38][39][40][41][42][43] At the end of the experiment, fasted mice were euthanized by an overdose intraperitoneal injection, set for each mouse, of sodium thiopental (50 mg kg −1 , B. Braun Medical SA, Barcelona, Spain) that was effective within 1 min, and the liver was subsequently collected, rapidly frozen, and stored at −80 °C until use. Plasma and hepatic lipid profile parameters were quantified as described in the ESI.…”
Section: In Vivo Study Designmentioning
confidence: 99%
“…The inhibitory capability remained high throughout GID mimicked in vitro and with the IC 50 value of 3.5 μg/ml. Finally, protamine‐derived peptides RPR (Arg‐Pro‐Arg) were assessed for their antiobesity and hypocholesterolemic effects in high‐fat diet (HFD)‐induced C57BL/6J mice (Mijiti et al., 2021). The findings demonstrated that serum cholesterol concentrations in the protamine and RPR groups were substantially lesser than in the control group.…”
Section: Health‐promoting Effects Of Food Bapsmentioning
confidence: 99%